Wahdah Al-Wujud By A 19th Malay Naqshabandi Scholar, Shaykh Islam Wan Sulaiman Wan Sidek - Muhammad Khairi Mahyuddin (Universiti Sains Islam Malaysia, 2024)
In the Malay world, the doctrine of wahdah al-wujud has been understood in various meanings either in pantheistic connotation or real unity (tawhid) of Allah. Most of the Malay society misperceive it in pantheistic meaning that imply the idea of incarnation (hulul) and union (ittihad). Shaykh Islam Wan Sulaiman Wan Sidek, a 19th Malay Naqshabandi exposes a wide meaning of wahdah al-wujud in his Malay Jawi script epistle, Hawd al-mawrud fi bayan wahdah al-wujud. The aim of this study is to describe Wan Sulaiman’s notion and approach in explaining wahdah al-wujud to his Malay contemporary society. This study employs historical and textual analytical study. The finding indicates that Wan Sulaiman’s idea in describing wahdah al-wujud is influenced by Ahmad al-Sirhindi’s teaching of his al-Maktubat. It can be conceived properly through purification of soul by participating in the Naqshabandi Order under the supervision of the shaykh. The true sense of wahdah al-wujud does not contain incarnation and union.